2001
DOI: 10.1056/nejm200106283442601
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of C-Reactive Protein for the Targeting of Statin Therapy in the Primary Prevention of Acute Coronary Events

Abstract: Statin therapy may be effective in the primary prevention of coronary events among subjects with relatively low lipid levels but with elevated levels of C-reactive protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
536
3
12

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,433 publications
(564 citation statements)
references
References 27 publications
13
536
3
12
Order By: Relevance
“…We present evidence that lower birth weight and shorter durations of breastfeeding both predict elevated concentrations of CRP in young adulthood, indicating increased risk for cardiovascular and metabolic diseases that are major health burdens in the USA and the UK. Clinical trials have demonstrated that statin therapy reduces CRP in healthy adults by 14.8-17.4% [53][54][55]. Our results suggest that the effects of breastfeeding on adult CRP are comparable, or larger, in magnitude.…”
Section: Discussionsupporting
confidence: 49%
“…We present evidence that lower birth weight and shorter durations of breastfeeding both predict elevated concentrations of CRP in young adulthood, indicating increased risk for cardiovascular and metabolic diseases that are major health burdens in the USA and the UK. Clinical trials have demonstrated that statin therapy reduces CRP in healthy adults by 14.8-17.4% [53][54][55]. Our results suggest that the effects of breastfeeding on adult CRP are comparable, or larger, in magnitude.…”
Section: Discussionsupporting
confidence: 49%
“…29). A more recent study determined that elevated levels of C-reactive protein, even in the absence of hyperlipidemia, are associated with an increased risk of coronary events (30). Statin therapy reduces the level of C-reactive protein independent of its effect on FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies point to IL-6 as a marker of cardiovascular disease as well as systemic inflammation (3)(4)(5)(6)(7)(8). IL-6 plasma levels are elevated in myocardial infarction, unstable angina, and atherosclerosis.…”
Section: Il-6 May Decrease Enos Expression In Atherosclerosis-mentioning
confidence: 99%
“…Although the APR is a rapid response to acute stress, chronic activation of the APR is associated with various diseases including cancer, autoimmune diseases, and coronary artery disease. For example, levels of acute phase effector proteins such as C-reactive protein (CRP), fibrinogen, and sICAM-1 are higher in patients with atherosclerosis or acute coronary syndromes compared with healthy controls (3)(4)(5)(6)(7)(8). The APR may play a role in the pathogenesis of endothelial dysfunction, an early stage in atherogenesis.…”
mentioning
confidence: 99%